The silent wife [compact disc, unabridged] - Slaughter, Karin, 1971- (Slaughter, Karin, 1971- Will Trent series., 2020)
Atlanta, Georgia. Present day. A young woman is brutally attacked and left for dead. The police search for the culprit but the trail goes cold, until Georgia Bureau of Investigation agent Will Trent makes a startling discovery. A prisoner in the state penitentiary tells Will that he recognizes the MO in the unsolved case. The attack looks identical to the crime he was convicted for ten years earlier. The imprisoned man has always maintained his innocence. Now, he's sure he was framed.